Sosialisasi Aksesibilitas dan Konektivitas Stasiun Kereta Api di Kecamatan Tanete Rilau, Kabupaten Barru, Sulawesi Selatan - Marly Valenti Patandianan; Ihsan .; Abdul Rachman Rasyid; Isfa Sastrawati; Laode Muh. Asfan Mujahid; Suci Anugrah Yanti; Angelia Khairunnisa; Agil Parwan (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
Apart from functioning as a place for loading and unloading goods and boarding and disembarking passengers, train stations also play a role in spurring economic growth in a region. In order for the train station to function well, efforts are needed to increase the station's contribution to society through improving train services. One of the important elements related to rail transportation services is accessibility and connectivity. Collaborative Service LBE activities take the form of outreach activities aimed at providing information and understanding regarding the accessibility and connectivity of the Tanete Rilau Railway Station (SKA-TR), in Tanete Rilau District, Barru Regency, South Sulawesi. Socialization activities were carried out in collaboration with Laloang Village in Kec. Tanete Rilau. The socialization participants were specifically 23 women who live in Laloang Village with various livelihoods. The method for implementing collaborative LBE community service activities is preceded by conducting a survey of the existing conditions of SKA-TR and outreach activities. This socialization activity explained the existing condition of SKA-TR through the presentation of photos of the survey results of the existing condition of SKA-TR, accessibility and connectivity material, and discussions. In measuring the success of activities, a pre-test was carried out before socialization and a post-test after socialization. The results of the pre-test and post-test qualitative analysis showed that participants' understanding and knowledge regarding the existing conditions of SKA-TR had increased to 74.53%. Meanwhile, the increase in understanding of SKA-RT accessibility and connectivity was 67.7%. These results indicate the success of the activity which is expected to indirectly attract participants' interest (specially the ladies) in using rail transportation.